Dimensions of Poverty and the Internal Relationship of Its Components with an Interpretive Structural Approach in the Imam Khomeini Relief Committee of Tabriz Metropolis - mehrdad Mohamadpour shatery; hoshang taghizadeh; sahar Khoshfetrat (تحقیقات کاربردی علوم جغرافیایی)
The phenomenon of poverty is a social, economic, cultural, and political reality that has long been one of the greatest human problems. The purpose of this study was to identify the factors affecting poverty and examine the internal relations and its leveling with an interpretive structural approach in the Imam Khomeini Relief Committee of Tabriz. In this regard, based on the factors extracted from literature, a questionnaire has been developed. In this phase, 41 indicators have been selected as the most important indicators affecting poverty at Imam Khomeini Relief Committee of Tabriz city. After obtaining appropriate validity and reliability for the questionnaire, it has been distributed among the statistical sample. After distributing the questionnaire, factor analysis was used to analyze the information and reduce the variables to dimensions. The results of factor analysis showed that about 68.3% of the total variance of variables was explained by 14 factors and about 31.7% of the variance was explained by other variables that were not measured. As a result, 14 factors have been identified as the most important factors affecting poverty. These 14 factors are important in order of importance: 1- Economic; 2- Social; 3- Individual; 4- Legal; 5- Family; 6; Environment; 7; Political; 8; Management; 9; Cultural; 10- Overseas; 11. Security; 12. Scientific; 13. Organizational; 14. Geographical. Finally, the interrelationships between factors and the leveling of poverty-related factors have been examined by presenting an extended structural-comparative model (ISM).